2014
DOI: 10.1038/srep07208
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion diffusion-weighted MR imaging of gliomas: efficacy in preoperative grading

Abstract: The preoperative grading of gliomas, which is critical for guiding therapeutic strategies, remains unsatisfactory. We aimed to retrospectively assess the efficacy of intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) in the grading of gliomas. Forty-two newly diagnosed glioma patients underwent conventional MR imaging, DWI, and contrast-enhanced MR imaging. Parameters of apparent diffusion coefficient (ADC), slow diffusion coefficient (D), fast diffusion coefficient (D*), and fraction of fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 27 publications
(45 reference statements)
6
89
1
2
Order By: Relevance
“…MB‐DWI images were processed by using the intravoxel incoherent motion (IVIM) imaging model in NordicICE using the same protocol as in previous publications, which yielded slow ADC (ie, D ), fast ADC (ie, D* ), slow fractional ADC (ie, 1‐f ), and fast fractional ADC (ie, f ) by using Eq. . Chi‐square maps were yielded by the chi‐square test on the sum of squared errors from the least‐squares fitting. SbSnormalo=f*eb*D*+(1f)*eb*D where S 0 and S b are the signal intensities at a b‐value of 0 sec/mm 2 and each b‐value other than 0 sec/mm 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MB‐DWI images were processed by using the intravoxel incoherent motion (IVIM) imaging model in NordicICE using the same protocol as in previous publications, which yielded slow ADC (ie, D ), fast ADC (ie, D* ), slow fractional ADC (ie, 1‐f ), and fast fractional ADC (ie, f ) by using Eq. . Chi‐square maps were yielded by the chi‐square test on the sum of squared errors from the least‐squares fitting. SbSnormalo=f*eb*D*+(1f)*eb*D where S 0 and S b are the signal intensities at a b‐value of 0 sec/mm 2 and each b‐value other than 0 sec/mm 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Both conventional (including T 1 ‐ and T 2 ‐weighted images) and advanced sequences, including dynamic contrast imaging (DCE), diffusion‐weighted imaging (DWI), and arterial spinal labeling (ASL) have been applied to preoperatively classify glioma. Although it is generally reported that advanced sequences are superior to conventional ones in classifying glioma grades, controversies still exist about the diagnostic accuracy of MRI . The major reason is that only a small number of MRI attributes from the limited MRI modalities were utilized, leaving a huge amount of valuable multimodal image information unused, not to mention reflecting the heterogeneity of gliomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The discernment between types and grading of gliomas were based on morphological (MR) imaging and metabolic (MRS) imaging [1,8]. However, in pursuance of making comparisons between groups (males/females, younger/older than 45 years old), this research utilized ADC values and rCBV due to the specificity of microscopic alterations arising in gliomas [6,7,[15][16][17]21]. Translated into medical terms, high grade gliomas are characterized by necrotic, edematous and hypervascular tissue (increased rCBV and decreased ADC value) and that will be the foundation of establishing the prospect of gliomas.…”
Section: A Patients Recruitmentmentioning
confidence: 99%
“…Anterior studies were conducted either on the basis of retrospective, social or statistical methods to ascertain a possible correlation between age, gender and occurrence of brain tumors [11][12][13][14][15][16][17][18]21].…”
Section: Introductionmentioning
confidence: 99%